TMEM16A Plays an Insignificant Role in Myocardium Remodeling but May Promote Angiogenesis of Heart During Pressure-overload - Zhang, Yaofang; Ye, Lingyu; Duan, Dayue Darrel; Yang, Hong; Ma, Tonghui (Frontiers in Physiology, 2022)
Background: Cardiac hypertrophy (CH) occurs with an increase in myocardium mass as an adaptive compensation to increased stress. Prolonged CH causes decompensated heart failure (HF). Enhanced angiogenesis by vascular endothelial growth factor (VEGF) is observed in hypertrophied hearts; impaired angiogenesis by angiotensin II (AngII) is observed in failing hearts. Angiogenesis is executed by vascular endothelial cells (ECs). Abnormal Ca2+ homeostasis is a hallmark feature of hypertrophied and failing hearts. Ca2+-activated chloride channel transmembrane protein 16A (TMEM16A) is expressed in cardiomyocytes and ECs but its role in heart under stress remains unknown. Methods: Pressure-overload-induced CH and HF mouse models were established. Echocardiography was performed to evaluate cardiac parameters. Quantitative real-time PCR, traditional and simple western assays were used to quantify molecular expression. Whole-cell patch-clamp experiments were used to detect TMEM16A current (ITMEM16A) and action potential duration (APD) of cardiomyocytes. VEGF and AngII were used separately in ECs culture to simulate enhanced or impaired angiogenesis, respectively. TMEM16A low-expressed and over-expressed ECs were obtained by siRNA or lentivirus transfection. Wound healing, tube formation and ECs spheroids sprouting assays were performed to assess migration and angiogenesis. Results: Neither TMEM16A molecular expression levels nor whole-cell ITMEM16A density varied significantly during the development of CH and HF. ITMEM16A comprises transient outward current, but doesn’t account for APD prolongation in hypertrophied or failing cardiomyocytes. In cultured ECs, TMEM16A knockdown inhibited migration and angiogenesis, TMEM16A overexpression showed opposite result. Promotion of migration and angiogenesis by VEGF was decreased in TMEM16A low-expressed ECs but was increased in TMEM16A over-expressed ECs. Inhibition of migration and angiogenesis by AngII was enhanced in TMEM16A low-expressed ECs but was attenuated in TMEM16A over-expressed ECs. Conclusion: TMEM16A contributes insignificantly in myocardium remodeling during pressure-overload. TMEM16A is a positive regulator of migration and angiogenesis under normal condition or simulated stress. TMEM16A may become a new target for upregulation of angiogenesis in ischemic disorders like ischemic heart disease.